Changes and Challenges of Financial Technology (FinTech) for the Banking Industry - Wu, Ruofei (Transactions on Economics, Business and Management Research, 2024)
With the rapid development of financial technology (FinTech), the traditional banking industry is facing unprecedented changes and challenges. This paper firstly discusses the definition, development history and key technologies of FinTech, and analyses its impact on the banking industry, including innovations in the areas of payment, lending and investment. At the same time, FinTech also brings challenges in various aspects such as regulation, security and privacy, competitive pressure and technological risks. To meet these challenges, traditional banks need to actively pursue technological innovation, optimise their business models, strengthen regulation and compliance, enhance their risk management capabilities, and continuously improve the customer experience. By establishing personalised services, optimising digital platforms and enhancing customer interactions, banks are able to better meet customer needs and enhance market competitiveness. This paper argues that in the era of fintech, traditional banks must respond flexibly to changes and seize market opportunities through innovation and cooperation to achieve sustainable development. Ultimately, the positive interaction between fintech and traditional banks will drive the continued progress of the entire financial industry.